Statistical design and analysis of stability studies - Chow, Shein-Chung, 1955- (Chapman & Hall/CRC biostatistics series, 2007)
Illustrating how stability studies play an important role in drug safety and quality assurance, this book introduces the basic concepts of stability testing. It focuses on short-term stability studies, and reviews several methods for estimating drug expiration dating periods.